2020
DOI: 10.1097/acm.0000000000003862
|View full text |Cite
|
Sign up to set email alerts
|

How Visual Arts–Based Education Can Promote Clinical Excellence

Abstract: A growing movement to integrate the arts and humanities into health professions education is afoot. While educators may easily conceive how artsbased teaching can improve clinically relevant skills such as observation and critical thinking, they may not realize it also has the potential to transform learners in myriad ways beyond sharpening these fundamental skills. In this article, the authors review how visual arts-based education can promote clinical excellence by enhancing communication and interpersonal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Participants opined that the module had developed their clinical observation skills. Critical analysis of art and visual thinking strategies (VTS) have been shown to increase clinical diagnostic skills (Chisolm 2020). A recent review mentions that results consistently indicate that participants nd that the incorporation of art into medical curricula was bene cial (Dalia et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Participants opined that the module had developed their clinical observation skills. Critical analysis of art and visual thinking strategies (VTS) have been shown to increase clinical diagnostic skills (Chisolm 2020). A recent review mentions that results consistently indicate that participants nd that the incorporation of art into medical curricula was bene cial (Dalia et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Art museum-based activities promote a wide range of skills in health professions education, including close observation, communication, critical thinking, and tolerance of ambiguity [7,[10][11][12][18][19][20]. Gaufberg and Williams reported on the use of the PRT with medical students and residents who particularly highlighted the PRT's ability to promote listening, communication, empathy, reflection, renewal, and the ability to "get in touch with their own humanity" [3 , p. 547].…”
Section: What We Know About the Prtmentioning
confidence: 99%
“…Not surprisingly, visual arts-based medical education programs sometimes take place in an art museum, providing a perhaps unfamiliar and potentially transformative space for arts-based teaching and learning [9]. Art museum-based teaching is an innovative approach to health professions learning, which can build clinical skills, foster personal growth, and support professional development [1,2,[6][7][8][10][11][12] and is rapidly becoming an area for faculty development across health care professions [13].…”
mentioning
confidence: 99%
“…Initially introduced as a teaching tool for primary education ( Nanavaty, 2018 ), VTS has been widely implemented in educating health care professionals, including nursing, medicine, pharmacy, and interprofessional education ( Klugman et al, 2011 ; Monahan et al, 2019 ; Moorman, 2015 ; Moorman et al, 2017 ; Poirier et al, 2020 ; Rana et al, 2020 ). Studies have reported that implementing VTS in health sciences education can help students strengthen their capacity for (1) observing and analyzing the patient during clinical rotation, (2) communicating with teams, (3) empathy, and (4) accepting diversity and ambiguity ( Chisolm et al, 2020 ). These capacities are essential for nursing students because assessing using human senses and empathetically communicating the assessed data are among the core competencies expected of nurses ( Monahan et al, 2019 ; Moorman et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%